Autologous Nanofragmented Lipoinjection (Nanofat) for the Treatment of Complex Anorectal Fistula Associated with Crohn's Disease - Alexandre Lopes de Carvalho; Lina Maria Goes de Codes; Alana Francisca Machado Melo; Flávia de Castro Ribeiro Fidelis; Bruna Fernandes Barreiro de Araújo; Fabio Pereira Soares de Araújo; Tiago Pereira de Castro; José Valber Lima Meneses (Journal of Coloproctology, 2025)
The management of complex anorectal fistulas associated with Crohn's Disease (CD) remains a significant clinical challenge, with current treatments achieving limited success in long-term remission. This article explores the application of autologous nanofragmented lipoinjection (Nanofat) for the treatment of Perianal Fistulizing Crohn's Disease (PFCD). Nanofat, derived from adipose tissue and containing mesenchymal stem cells, offers the potential for tissue regeneration and immune modulation in the inflammatory environment of perianal CD. A patient with a chronic fistula, previously treated with Seton and maintained biologic therapy, underwent liposuction and nanofragmentation of adipose tissue. The resulting Nanofat was injected into the fistula tract following surgical debridement. The patient demonstrated complete healing with no recurrence of symptoms after six months, showcasing the efficacy of this technique. This autologous approach is low-cost, minimally invasive, and reproducible, with promising clinical outcomes. The addition of nanofragmented fat enhances tissue penetration and fat survival compared with traditional Microfat, increasing the chances of successful fistula repair. Further controlled studies comparing Nanofat with other established fistula repair methods are warranted to assess its long-term efficacy and standardize treatment protocols.